2014
DOI: 10.7448/ias.17.4.19649
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of monoclonal gammopathy in HIV patients in 2014

Abstract: Introduction In non-HIV patients, Monoclonal Gammopathy of Undetermined Significance (MGUS) is associated with an increased risk of subsequent development of haematologic malignancies, especially multiple myeloma (MM) and it has been recently demonstrated that MM is always preceded by a MGUS phase. A higher prevalence of MGUS and MM has been observed in HIV patients compared to the general population. Nevertheless, it has been shown that MGUS in the context of HIV can disappear with antiretroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…A higher prevalence rate of MGUS has been reported in HIV-infected persons, ranging between 3 and 26%. Compared to the general population, MGUS in HIV-infected patients occurs at much younger age and, often disappers after effective antiretroviral treatment (ART) 7 9 .…”
mentioning
confidence: 99%
“…A higher prevalence rate of MGUS has been reported in HIV-infected persons, ranging between 3 and 26%. Compared to the general population, MGUS in HIV-infected patients occurs at much younger age and, often disappers after effective antiretroviral treatment (ART) 7 9 .…”
mentioning
confidence: 99%
“…The most likely HIV transmission route for this patient was a blood transfusion that occurred in 1978, which is 30 years prior to the diagnosis of MM and 33 years before diagnosis of HIV. Although monoclonal gammopathies of undetermined significance (MGUS) are frequent in HIV-infected patients [ 7 , 8 ], our patient presented with plasma M-protein >30 g/L at diagnosis, which classifies for MM according to the International Myeloma Working Group [ 9 ]. Nevertheless, a long-term followup of MGUS patients at the Mayo Clinic revealed that around 16% of MGUS cases evolved towards a MM, with a median time of progression of 10.6 years [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective, observational study on 69 patients with MGUS, 68% of the 57 that were tested for H. pylori showed signs of this infection ( 38 ). A high prevalence of MGUS has also been observed in patients infected by human immunodeficiency virus (HIV), compared with the general population ( Table 2 ) ( 39 ). These findings support the hypothesis of chronic antigen stimulation as a factor in the pathogenesis of MGUS.…”
Section: Mgus and Infectionsmentioning
confidence: 99%